A method for preparing high melting point carbon oxide composite ceramics

The high-melting point carbon oxide composite ceramics are prepared in one step through discharge plasma sintering technology, which solves the problems of insufficient oxidation resistance and complex preparation process of existing ceramic materials, and achieves high density, low porosity and uniform composition of ceramic materials , suitable for thermal protection applications in high temperature environments.

CN118754650BActive Publication Date: 2025-02-21YUNNAN HUIDA NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410901424.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-02-21
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

The existing ultra-high temperature ceramic materials have insufficient oxidation resistance under high temperature environments, and the preparation process has problems such as difficult to accurately control the component ratio and densification of ceramic blocks.

Method used

Carbide powder and oxide powder are used as raw materials to prepare high-melting point carbon oxide composite ceramic blocks in one step through discharge plasma sintering technology to achieve high density, low porosity and uniform composition of heterogeneous carbon oxide ceramics.

Benefits of technology

The preparation of high-melting point carbon oxide composite ceramics has high purity, low porosity and excellent high-temperature performance. It is suitable for the application of the new generation of thermal protection structural ceramics in aerospace, nuclear energy and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754650B_ABST
    Figure CN118754650B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of high-temperature protective ceramics, and discloses a method for preparing high-melting-point carbon oxide composite ceramics, comprising the following steps: weighing the mass of HfO2 and TiC powders; putting them into a planetary ball mill and mixing them evenly; then putting them into an oven to fully dry and sieve; adhering graphite paper to the inner cavity of a graphite mold; pouring the dried raw material powder into the graphite mold, and pre-pressing to expel as much air as possible; putting the graphite mold loaded with the raw material powder into a discharge plasma sintering furnace, and sintering at high temperature and high pressure under the auxiliary action of plasma; after the sintering furnace is cooled, demolding to obtain a composite ceramic block. The present invention adopts the above-mentioned method for preparing a high-melting-point carbon oxide composite ceramic, which has a simple process, a short cycle, and flexible component design, and can achieve multiphase carbon oxide ceramics with high density, low porosity, and uniform composition, providing an innovative and efficient preparation method for the application of a new generation of thermal protection structural ceramics in aerospace, nuclear energy and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high temperature protection ceramics, and in particular to a method for preparing high melting point carbon oxide composite ceramics. Background Art

[0002] With the continuous progress of the human aerospace industry, people have put forward higher requirements for the performance of hypersonic aircraft, including higher service temperature, longer service life and stronger corrosion resistance. However, when the aircraft flies at the speed of sound, the air at the tip and leading edge of the shape is rapidly compressed and forms shock waves, which produces extreme radiation and convection heating. This requires that the structural materials responsible for the thermal protection of the outer end have sufficient temperature resistance, mechanical properties and strong oxidation resistance to withstand harsh extreme environments.

[0003] Due to the existence of the shock layer, the maximum temperature of the aircraft surface can reach over 2000℃. Therefore, having an extremely high melting point becomes a prerequisite for the selection of thermal protection structural materials. Metal materials have excellent comprehensive properties and are the first choice for traditional structural materials. However, due to their relatively low melting points, metal materials are difficult to serve in ultra-high temperature environments. For example, the maximum service temperature of nickel-based high-temperature alloys is only 1400℃.

[0004] Ultra-high temperature ceramics (UHTCs) are generally defined as compounds with a melting point above 3000°C, mainly composed of boron, carbon or nitrides of transition metals. Among them, carbides, in particular, are the most promising candidate materials to meet high temperature performance requirements due to their extremely high melting points and excellent high-temperature mechanical properties. However, traditional ultra-high temperature carbides, such as ZrC and HfC, usually form a loose oxide layer on the surface after oxidation, and have poor oxidation resistance, so their application is greatly limited. Oxide ceramics are ideal for dealing with oxidizing environments due to their intrinsic antioxidant properties. However, the relatively low melting point of oxides and their poor mechanical properties at high temperatures have hindered their further development.

[0005] In recent years, the emergence of new carbon oxides has provided a new strategy for people to further improve the antioxidant properties of carbides. Researchers continue to explore the intrinsic properties of carbon oxides, greatly accelerating the pace of development of strong antioxidant materials. For example, Wen et al. from South China University of Technology (Corros. Sci. 207 (2022) 110574) used carbon thermal reduction to prepare a face-centered cubic structure (Hf 0.25 Zr 0.25 Nb 0.25 Ti 0.25 )(C 0.5 O 0.5 ) high entropy carbon oxide powder. The oxidation test results show that (Hf 0.25 Zr0.25 Nb 0.25 Ti 0.25 )C high entropy carbide, the prepared high entropy carbon oxide sample has a higher initial oxidation temperature and a slower oxidation rate, showing better oxidation resistance, which is due to its higher oxidation activation energy and Gibbs free energy of oxidation reaction. Chen et al. from Central South University (Adv. Powder Mater. (2023) 100168.) found that after ultra-high temperature oxidation of (Hf, Ti) C solid solution ceramics at 2500 ° C, a main structure consisting of a small amount of carbon-doped hafnium oxide and Ti-rich carbon oxide appeared in the oxide layer, and the structure remained stable as the oxidation time increased. In addition, the team also found that (Hf, Zr, Ti) C, (Hf, Zr, Ti, Nb) C and (Hf, Zr, Ti, Ta) C multi-carbide ceramics also showed similar oxide layer structures after ultra-high temperature oxidation at 2500 ° C (J. Adv. Ceram. 13 (2024) 332-344). This phenomenon shows that the combination of dual-phase carbon oxides can withstand the test of high-temperature and long-term oxidation and has great potential for application in high-temperature oxidation environments.

[0006] At present, the mainstream method for preparing carbon oxide ceramics is the carbothermal reduction method, which uses the balance of reduction reaction to achieve the coexistence of C and O in ceramic materials. However, the carbothermal reduction method has the following two major limitations: First, the essence of the carbothermal reduction method is a carbothermal reduction reaction, which is a chemical equilibrium reaction affected by multiple factors, so it is difficult to achieve precise control of the target product composition ratio; second, this method is only applicable to the preparation of carbon oxide ceramic powders. If carbon oxide ceramic blocks are to be prepared, further pressure sintering and densification are required.

[0007] The present invention innovatively uses carbide powder and oxide powder as raw materials and adopts spark plasma sintering technology to prepare multiphase carbon oxide ceramic blocks in one step. The preparation process is simple, the cycle is short, and the component design is flexible, which greatly expands the composition design range of carbon oxide ceramics, is conducive to optimizing the content of each component in multiphase carbon oxide ceramics, and realizes the preparation of high-performance carbon oxide ceramics. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing high-melting-point carbon oxide multiphase ceramics, which has a simple process, short cycle and flexible component design, and can achieve multiphase carbon oxide ceramics with high density, low porosity and uniform composition, providing an innovative and efficient preparation method for the application of a new generation of thermal protection structural ceramics in aerospace, nuclear energy and other fields.

[0009] To achieve the above object, the present invention provides a method for preparing a high melting point carbon oxide composite ceramic, comprising the following steps:

[0010] S1. Weigh the mass of HfO2 and TiC powder;

[0011] S2. Put the weighed powder into a planetary ball mill and mix it evenly using a high-energy ball mill;

[0012] S3, then put it into the oven to fully dry and sieve;

[0013] S4. Graphite paper is adhered to the inner cavity of the graphite mold to prevent the raw material powder from directly contacting the mold;

[0014] S5. Pour the dried raw material powder into the graphite mold and pre-press to expel as much air as possible;

[0015] S6, placing the graphite mold loaded with raw material powder into a spark plasma sintering furnace, and sintering at high temperature and high pressure under the assistance of plasma;

[0016] S7, after the sintering furnace is cooled, demoulding is performed to obtain a composite ceramic block.

[0017] Furthermore, in step S1, the purity of HfO2 powder and TiC powder is ≥99%, the particle size of HfO2 powder is 100nm, the particle size of TiC powder is 1-3μm, and the molar mass ratio of HfO2 powder to TiC powder is 3-5:1.

[0018] Furthermore, in step S2, the ball milling speed is 150-250 rpm, the ball milling time is 12-15 hours, the ball milling medium is anhydrous ethanol, the ball milling jar and the ball material are zirconium oxide, and the ball-to-material ratio is 5-7:1.

[0019] Furthermore, in step S3, the oven temperature is 40-50° C., the drying time is ≥40 h, and the sieve mesh number is ≥100 mesh.

[0020] Furthermore, the sintering conditions in step S6 are: vacuum sintering atmosphere, vacuum degree in the sintering furnace is less than 10 Pa, sintering temperature is 1800-2000° C., and heat preservation is 10-20 minutes.

[0021] Further, the temperature is raised from room temperature to the sintering temperature at a heating rate of 100° C. / min, and then maintained at the sintering temperature.

[0022] The present invention also provides a high melting point carbon oxide composite ceramic, which is prepared by the above preparation method.

[0023] Furthermore, the molecular formula of the high melting point carbon oxide composite ceramic is HfO a C b —TiC c O d , where a+b=2, a>b; c+d=1, c>d.

[0024] The advantages and positive effects of the preparation method of a high melting point carbon oxide composite ceramic described in the present invention are:

[0025] 1. The present invention mixes HfO2 powder and TiC powder by high-energy ball milling, uses spark plasma sintering technology to make the two powders undergo solid-phase diffusion reaction at high temperature, and sinters them to densify under pressure, thereby obtaining the target multiphase ceramic block in one step.

[0026] 2. The high melting point carbon oxide composite ceramic prepared by the present invention is composed of TiC with face-centered cubic structure. c O d Ceramics and monoclinic HfO a C b The composition is high in purity, low in porosity and high in efficiency, and it is expected to be extended to the preparation of carbon oxide composite ceramics with other components, and has great application potential.

[0027] 3. The present invention has a simple process, a short cycle, and flexible component design, and can achieve multiphase carbon oxide ceramics with high density, low porosity, and uniform composition, providing an innovative and efficient preparation method for the application of a new generation of thermal protection structural ceramics in aerospace, nuclear energy and other fields.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a macroscopic morphology of the carbon oxide composite ceramic prepared in Example 1 of the present invention;

[0030] Figure 2 This is a microscopic morphology of the carbon oxide composite ceramic prepared in Example 1 of the present invention;

[0031] Figure 3 The XRD result of the carbon oxide composite ceramic prepared in Example 1 of the present invention;

[0032] Figure 4 This is the EDS line scan result of the carbon oxide composite ceramic prepared in Example 1 of the present invention;

[0033] Figure 5 This is a microscopic morphology of the carbon oxide composite ceramic prepared in Example 2 of the present invention;

[0034] Figure 6 XRD results of the carbon oxide composite ceramic prepared in Example 2 of the present invention;

[0035] Figure 7 This is the EDS line scan result of the carbon oxide composite ceramic prepared in Example 2 of the present invention;

[0036] Figure 8This is a microscopic morphology of the carbon oxide composite ceramic prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0039] Example 1

[0040] S1. Weigh HfO2 powder and TiC powder in a molar ratio of 5:1 for later use, wherein the particle size of HfO2 powder is 100nm, the purity is ≥99.9%, and the particle size of TiC powder is 1-3μm, the purity is ≥99.5%;

[0041] S2. Put the weighed raw material powder into a planetary ball mill of zirconium oxide and mix them evenly by high-energy ball milling for 12 hours, wherein the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 5:1, and the rotation speed is 200 rpm;

[0042] S3, put the mixed raw material powder into a 40°C oven, fully dry for 40 hours, and pass through a 100-mesh sieve;

[0043] S4, adhering graphite paper to the inner cavity of the graphite mold;

[0044] S5, pour the dried raw material powder into the graphite mold, and use 1T pressure to pre-press to expel as much air as possible;

[0045] S6, placing the graphite mold loaded with raw material powder into a plasma sintering furnace, heating the temperature from room temperature to 1900°C at a heating rate of 100°C / min, and keeping the temperature at the set temperature for 20 minutes;

[0046] S7, after cooling in the furnace, demoulding with a hydraulic press to obtain 5HfO a C b -1TiC c O d Ceramic block.

[0047] Example 2

[0048] S1. Weigh HfO2 powder and TiC powder in a molar ratio of 3:1 for later use, wherein the particle size of HfO2 powder is 100nm, the purity is ≥99.9%, and the particle size of TiC powder is 1-3μm, the purity is ≥99.5%;

[0049] S2. Put the weighed raw material powder into a planetary ball mill of zirconium oxide and mix them evenly by high-energy ball milling for 14 hours, wherein the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 6:1, and the rotation speed is 150 rpm;

[0050] S3, put the mixed raw material powder into a 40°C oven, fully dry for 40 hours, and pass through a 100-mesh sieve;

[0051] S4, adhering graphite paper to the inner cavity of the graphite mold;

[0052] S5, pour the dried raw material powder into the graphite mold, and use 1T pressure to pre-press to expel as much air as possible;

[0053] S6, placing the graphite mold loaded with the raw material powder into a plasma sintering furnace, heating the temperature from room temperature to 1900°C at a heating rate of 100°C / min, and keeping the temperature at the set temperature for 20 minutes;

[0054] S7, after cooling in the furnace, demoulding with a hydraulic press to obtain 3HfO a C b -1TiC c O d Ceramic block.

[0055] Example 3

[0056] S1. Weigh HfO2 powder and TiC powder in a molar ratio of 5:1 for later use, wherein the particle size of HfO2 powder is 100nm, the purity is ≥99.9%, and the particle size of TiC powder is 1-3μm, the purity is ≥99.5%;

[0057] S2. Put the weighed raw material powder into a planetary ball mill of zirconium oxide and mix them evenly by high-energy ball milling for 12 hours, wherein the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 5:1, and the rotation speed is 200 rpm;

[0058] S3, put the mixed raw material powder into a 40°C oven, fully dry for 40 hours, and pass through a 100-mesh sieve;

[0059] S4, adhering graphite paper to the inner cavity of the graphite mold;

[0060] S5, pour the dried raw material powder into the graphite mold, and use 1T pressure to pre-press to expel as much air as possible;

[0061] S6, placing the graphite mold loaded with the raw material powder into a plasma sintering furnace, heating the temperature from room temperature to 1700°C at a heating rate of 100°C / min, and keeping the temperature at the set temperature for 20 minutes;

[0062] S7, after cooling in the furnace, demoulding with a hydraulic press to obtain 5HfO a C b -1TiC c O d Ceramic block.

[0063] The parameter settings are shown in Table 1:

[0064] Table 1

[0065]

[0066] Performance Testing

[0067] Figure 1 This is the macroscopic morphology of the carbon oxide composite ceramic prepared in Example 1.

[0068] Figure 2 The microscopic morphology of the carbon oxide composite ceramic prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the carbon oxide composite ceramic prepared in Example 1 is very dense, no cracks are observed, and the two phases are dispersed and uniformly distributed.

[0069] Figure 3 The XRD results of the carbon oxide composite ceramics prepared in Example 1 are as follows: Figure 3 It can be seen that the carbon oxide ceramic block prepared in Example 1 has only diffraction peaks similar to monoclinic HfO2 and face-centered cubic TiC, but the peak positions are slightly offset. This is because HfO2 and TiC undergo solid-phase diffusion at high temperature, and a small amount of C atoms diffuse into the HfO2 lattice to form HfO a C b phase, a small amount of O atoms diffuse into the TiC lattice to form TiC c O d In addition, it is also shown that the ceramic block obtained in Example 1 is pure and free of other impurities.

[0070] Figure 4 The EDS line scan results of the carbon oxide composite ceramic prepared in Example 1 are as follows: Figure 4 It can be seen that the carbon oxide composite ceramics prepared in Example 1 are tightly combined with each other, and there is a uniform composition transition at the interface, and the preparation of the two-phase carbon oxide is successfully achieved.

[0071] Figure 5 The microscopic morphology of the carbon oxide composite ceramic prepared in Example 2 is shown in FIG. Figure 5 It can be seen that the carbon oxide ceramic block prepared in Example 2 is very dense, no cracks are observed, and the two phases are dispersed and uniformly distributed.

[0072] Figure 6 The XRD results of the carbon oxide composite ceramics prepared in Example 2 are as follows: Figure 6 It can be seen that the carbon oxide ceramic block prepared in Example 2 has only diffraction peaks similar to monoclinic HfO2 and face-centered cubic TiC, without other impurities.

[0073] Figure 7 The EDS line scan results of the carbon oxide composite ceramic prepared in Example 2 are as follows: Figure 7It can be seen that the carbon oxide ceramic blocks prepared in Example 2 are tightly combined with each other, and there is a uniform composition transition at the interface, and the preparation of the dual-phase carbon oxide is successfully achieved.

[0074] Figure 8 The microscopic morphology of the carbon oxide composite ceramic prepared in Example 3 is shown in FIG. Figure 8 It can be seen that the distribution of the two phases of the carbon oxide ceramic block prepared in Example 3 is not uniform, and there is obvious segregation, which indicates that the sintering temperature is too low and the solid phase diffusion reaction is incomplete.

[0075] Therefore, the present invention adopts the above-mentioned method for preparing a high-melting-point carbon oxide multiphase ceramic, which has a simple process, a short cycle, and flexible component design, and can achieve high-density, low-porosity, and uniform composition multiphase carbon oxide ceramics, providing an innovative and efficient preparation method for the application of a new generation of thermal protection structural ceramics in aerospace, nuclear energy and other fields.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing high melting point carbon oxide composite ceramics, characterized in that: The following steps are involved: S1. Weigh the mass of HfO2 and TiC powders, wherein the molar mass ratio of HfO2 powder to TiC powder is 3-5:1; S2. Put the weighed powder into a planetary ball mill and mix it evenly using a high-energy ball mill; S3, then put it into an oven to fully dry and sieve; S4. Graphite paper is adhered to the inner cavity of the graphite mold to prevent the raw material powder from directly contacting the mold; S5. Pour the dried raw material powder into the graphite mold and pre-press to expel as much air as possible; S6, placing the graphite mold loaded with raw material powder into a spark plasma sintering furnace, and sintering at high temperature and high pressure under the assistance of plasma; The sintering conditions are: vacuum sintering atmosphere, vacuum degree in the sintering furnace is less than 10Pa, sintering temperature is 1800-2000℃, and heat preservation is 10-20min; S7, after the sintering furnace is cooled, demoulding is performed to obtain a composite ceramic block.

2. The preparation method according to claim 1, characterized in that: In step S1, the purity of HfO2 powder and TiC powder is ≥99%, the particle size of HfO2 powder is 100nm, and the particle size of TiC powder is 1-3μm.

3. The preparation method according to claim 1, characterized in that: In step S2, the ball milling speed is 150-250 rpm, the ball milling time is 12-15 hours, the ball milling medium is anhydrous ethanol, the ball milling jar and the ball material are zirconium oxide, and the ball-to-material ratio is 5-7:

1.

4. The preparation method according to claim 1, characterized in that: In step S3, the oven temperature is 40-50° C., the drying time is ≥40 h, and the sieve mesh number is ≥100 mesh.

5. The preparation method according to claim 1, characterized in that: In step S6, the temperature is raised from room temperature to the sintering temperature at a heating rate of 100° C. / min, and then maintained at the sintering temperature.

6. A high melting point carbon oxide composite ceramic, characterized in that: The preparation method is described in any one of claims 1 to 5.

7. The high melting point carbon oxide composite ceramic according to claim 6, characterized in that: Its molecular formula is HfO a C b —TiC c O d , where a+b=2, a>b; c+d=1, c>d.

Citation Information

Patent Citations

  • Ceramic composite material and method for producing same

    CN1874973A